Intratumoral immunotherapy prior to cancer surgery, a promising therapeutic approach - Silihe Kamga, Kevine; Fiering, Steven (Frontiers in Immunology, 2025)
Cancer immunotherapy has made astonishing progress in the last 10–15 years, and the rate of progress is accelerating. However, only 20 to 40% of patients benefit from this therapy with most immunotherapy applied post discovery of metastatic disease when therapeutic impact is more difficult to achieve. The first line of treatment for many patients following diagnosis is surgery. Neoadjuvant immunotherapy, i.e. administration of immune therapy prior to surgery, has the potential to improve overall survival rates. Many patients without detectable metastases are diagnosed with a high risk of future metastasis and could benefit from effective neoadjuvant immunotherapy. An ideal neoadjuvant immune therapy will stimulate immune response against the identified tumor as well as undetected metastasis and be safe with minimal adverse events. In addition, the antitumor immune response it generates should not be blocked by subsequent surgery and should not delay the normal timeline of surgery. Finally, it should be relatively inexpensive. These features describe intratumoral immunotherapy (ITIT), a therapeutic approach that directly administers immune stimulatory agents or treatments into the tumor. By delivering the therapy directly into the tumor, it enhances local drug concentration while minimizing nonspecific immune activation and adverse events associated with systemic immunotherapy. ITIT can generate effective local immune response against tumor antigens, which expands the pool of tumor-recognizing effector T cells. ITIT induces and activates tumor specific T cell within days after the treatment, so surgery is not delayed. Tumor-recognizing effector T cells generated locally attack cancer both locally and systemically, targeting metastasis through the “abscopal effect”. Neoadjuvant ITIT options are extensive and expanding and need research into optimal options to combine and associated dosing and timing. With the needed effort, neoadjuvant ITIT will develop into a safe, rapid and effective addition to current cancer therapies.